(untitled) (Revista Innova Educación, 2021)
Digital competences are increasingly making their way as essential to achieve a true information and knowledge society. Identifying, describing and evaluating them are vital processes to differentiate them from other skills necessary for working with ICT. These competences are an important need in the current context of COVID 19, both due to their deficiencies in the general population and in the educational field. In this review of the literature, the differences of this concept with others such as information literacy and digital literacy are observed, both from their areas of study, to the dimensions and standards for their implementation and evaluation. Evidence is provided of the importance of the digital divide to achieve them, and of how they can be developed from different strategies such as the Inverted Classroom. The results suggest that this methodology could be suitable in the context of current education.